577. Cord Blood Protective Antibodies Seroprevalence against Diphtheria, Pertussis, Measles, Mumps and Rubella at Birth among Healthy Term Indian Neonates. (15th December 2022) - Verma, Sanjay; James, Deepak; Lavanya, Jula; Rawat, Amit; Venkataseshan, Sundaram; Aggarwal, Neelam
Abstract: Background: The resurgence of vaccine preventable diseases in young infants is a matter of concern worldwide. Cord blood antibodies seroprevalence against various vaccine preventable diseases could reflect protection rates among adults, which could be important in providing protection in early infancy of newborn baby. Tdap vaccination is not yet part of immunization program for pregnant women in India. Methods: Apparently healthy term newborns, delivered at a tertiary care hospital in Northern India, over two-year period were enrolled after taking informed written consent from their parents, and their cord blood sample was collected at birth. Ethical clearance was obtained from Institute Ethics Committee before starting enrollment. Results: A total of 160 newborns (M:F=86:74) were enrolled. In our study, antibodies (IgG) against diphtheria toxin (DT) were > 0.1 IU/ml in 44.4% (71/160), 0.01 to 0.1 IU/ml in 53.1% (85/160) and < 0.01 IU/ml in 2.5% (4/160). Only 44.4% of them were fully protected at birth against diphtheria. Antibodies (IgG) against pertussis toxin (PT) > 40 U/ml were seen in 41.2% (66/160). Out of these 66 children, 23 had titers > 100 U/ml. Total of 58.8% (94/160) children had antibodies < 40 U/ml. Out of these 94 children, 48 had titers < 20 U/ml. Since correlates of protection in pertussis are not defined; those having titers > 100 U/ml i.e. 14.3% were most protected; while those having titers < 20 U/ml were least protected. Antibodies (IgG) against measles antigen were >12 IU/ml in 88.8% (142/160). Antibodies (IgG) against mumps antigen were >12 IU/ml in 83.1% (133/160). Antibodies (IgG) against rubella antigen were >12 IU/ml in 83.7% (134/160). Conclusion: Protective antibodies against diphtheria and pertussis toxins were less in the studied newborns at birth making them susceptible to these diseases in early infancy, before primary vaccination commences. Tdap vaccination for pregnant mothers in India could help in improving these titers and protection in early infancy. Protective antibodies against measles, mumps and rubella in studied newborns at birth were satisfactory. For further enhancing protection, especially against rubella, one dose of MMR vaccine may be advised for women in child bearing age. Acknowledgement: PGI Intramural Research Grant Disclosures: All Authors : No reported disclosures.